An investigation of the stepped thermography technique for defects evaluation in GFRP materials. (March 2019) - Palumbo, Davide; Cavallo, Pasquale; Galietti, Umberto
Abstract: The ability of thermography to detect defects in composite materials has been demonstrated and showed in various works and in many applications. In this regard, various NDT techniques are currently used for defect detection in composites such as Lock-in Thermography (LT), Pulsed (PT) Stepped Thermography (ST/SH), all of which have their own peculiarities and capabilities. A critical aspect concerns the overall lengthy time required for testing and analysis of thermographic data above all, for large structure where it is necessary a scanning approach. In this work, two algorithms based on the stepped thermography approach were investigated in quantitative way with the aim to optimizing the testing parameters and data analysis in terms of testing time and signal to noise ratio. In particular, several tests were carried out on a sample specimen with simulated defects and the well-established lock-in thermography technique has been used as comparison.